Ceratocystis platani is killing plane trees in Istanbul (Turkey). Issue 1 (1st August 2017) - Lehtijärvi, A.; Oskay, F.; Doğmuş Lehtijärvi, H. T.; Aday Kaya, A. G.; Pecori, F.; Santini, A.; Woodward, S.
Summary: Ceratocystis platani was detected at several locations in the European side of Istanbul, causing severe dieback and mortality, mainly on Platanus × acerifolia imported from Italy approximately 160 years ago, but also on Platanus orientalis . In the work reported here, the causal agent of the dieback and mortality was identified based on morphological characteristics in culture and internal transcribed spacer (ITS) sequencing, confirming the presence of C. platani in Turkey. All analysed C. platani isolates from Istanbul shared the same ITS sequence with European C. platani strains available in the NCBI, but differed from other species previously ascribed to the Ceratocystis fimbriata species complex. Pathogenicity of C. platani was proven by inoculation onto 25‐cm‐long and 4–9 mm diam. P. orientalis twigs and the causal agent reisolated from symptomatic tissues. In a survey of 976 Platanus in streets and parks of Istanbul, 26.5% of trees showed symptoms of C. platani infections, whilst 5.6% were dead. The proportion of symptomatic trees was higher where management interventions, such as topping or pruning and felling infected trees had been carried out.